Repeated-sprint training with low lung volume voluntary hypoventilation performed continuously throughout each set in healthy females - Devantay, Léa; Millet, Grégoire P.; Raberin, Antoine (Frontiers in Physiology, 2026)
PurposeThis study aimed to investigate the acute responses induced by a session of repeated-sprint training in hypoxia (RSH) induced by voluntary hypoventilation at low lung volume (VHL) performed continuously throughout the exercise in healthy females.MethodsThirteen females performed, in a randomized order, two sessions of repeated sprints (three sets of eight 10-s all-out sprints): with normal breathing (RSN) vs. with VHL performed continuously throughout each set (RSH-VHL). Peak and mean power output, heart rate, stroke volume, cardiac output, pulse oxygen saturation, muscle oxygenation in the vastus lateralis and the biceps brachii, blood lactate concentration, rate of perceived exertion and perceived difficulty of breathing and pedalling were assessed.ResultsRSH-VHL did not induce desaturation (97.5 ± 2.0 for RSH-VHL vs. 98.0% ± 1.6% for RSN; p = 0.243) nor greater muscle deoxygenation in the vastus lateralis (mean minimum tissue saturation index: 62.3% ± 4.3% vs. 61.5% ± 4.4%; p = 0.193) or the short head of the biceps (36.6% ± 10.0% vs. 34.2% ± 13.7%; p = 0.320). Significantly lower training load indices were observed from the first set onwards during RSH-VHL compared with RSN: mean peak power output (311 ± 45 vs. 382 ± 46 W; p < 0.001) and blood lactate concentration (6.8 ± 2.9 vs. 9.9 ± 3.0 mmol/L; p = 0.003). The perceived difficulty of breathing was higher during RSH-VHL than RSN from the first set onwards (8.2 ± 2.2 vs. 6.0 ± 0.9; p = 0.022).ConclusionThis study showed that, although participants reported increased breathing difficulty during RSH-VHL performed continuously, this condition did not result in significant systemic or local hypoxia. Moreover, it led to a lower training load compared to RSN. When VHL is performed continuously throughout each set, rather than only during sprints, it may be too strenuous, inducing a significant reduction in training load.